2016
DOI: 10.1292/jvms.15-0381
|View full text |Cite
|
Sign up to set email alerts
|

Blood biochemical values in Japanese Black calves in Kagoshima Prefecture, Japan

Abstract: ABSTRACT. To obtain blood biochemical basic data of Japanese Black calves in Kagoshima Prefecture, Japan, blood samples were obtained from 582 clinically healthy calves on 27 farms. Calves were divided into three stages: the suckling stage (between 14 and 90 days of age, n=191), the early growing stage (between 91 and 180 days of age, n=200) and the late growing stage (between 181 and 270 days of age, n=191). The mean concentration of total cholesterol, triglyceride, nonesterified fatty acids, calcium and zinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 16 publications
4
13
1
Order By: Relevance
“…The width of ALP distribution for Holstein Friesian cattle reported by Sato et al [11] is similar to the width observed in the present study. No ALP measurements were found for mature Japanese black cattle, but animals under the age of one were more than four times the range of ALP in the present study [12]. This finding is likely due to an increase in bone-type ALP during rapid growth.…”
Section: Plos Onecontrasting
confidence: 80%
“…The width of ALP distribution for Holstein Friesian cattle reported by Sato et al [11] is similar to the width observed in the present study. No ALP measurements were found for mature Japanese black cattle, but animals under the age of one were more than four times the range of ALP in the present study [12]. This finding is likely due to an increase in bone-type ALP during rapid growth.…”
Section: Plos Onecontrasting
confidence: 80%
“…, p < 0.05) were signi cantly increased in Group H, which indicated that the higher dietary energy and protein levels remarkably improved the growth performance and carcass characteristics of goats in our previous study. In addition, other studies reported that the serum biochemical parameters were sensitive indicators of health status of animals [37][38][39]. In our previous study, few differences in serum biochemical indices between Groups C and H (p > 0.05) suggested the similar healthy status of goats in the two groups [28].…”
Section: Discussionmentioning
confidence: 90%
“…On day 18, a complete blood count revealed a slight elevation of the red blood cell (RBC) count and thrombocytosis, but normal white blood cell (WBC) count (Table 1) [20, 24]. High level of lactate dehydrogenase (LDH), hypoproteinemia and hypoalbuminemia were evident upon serum biochemical examination [20, 22].…”
Section: Case Presentationmentioning
confidence: 99%
“…High level of lactate dehydrogenase (LDH), hypoproteinemia and hypoalbuminemia were evident upon serum biochemical examination [20, 22].…”
Section: Case Presentationmentioning
confidence: 99%